PERLINDUNGAN HUKUM HAK PENCIPTA LAGU DAN MUSIK YANG DIKOMERSIALISASI DI PLATFORM DIGITAL YOUTUBE TANPA IZIN - Liza Marina; Fahririn Fahririn; M Ridwan (Universitas Suryakancana, 2023)
Repeating songs or covering songs uploaded on a digital platform is done in practice, but among them there is covering the songs and music commercially without the permission of the Creator and the Related Rights Owner. This research is carried out using normative legal methods through legislative approaches. The study discusses the application of the economic rights protection of Creators and Related Rights Holders on songs reproduced commercially without permission on the uploaded digital platforms of yuotube and the role of LMKN in protecting the copyrights of songs and music uploaded on the digital platform of youtube.Â Based on this legal normative study, it is concluded that the protection of recorded and unrecorded song and music works remains protected by law as well as the role of the National Collective Management Agency in collecting royalty on song and musical works on digital platforms is part of the protection granted to Creators and Owners of related rights over their economic rights.Keywords: Copyright, cover song, digital platform, LMKN